Faktor-faktor yang mempengaruhi perpindahan merek Asus ke merek lain (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to examine "Analysis of the influence of dissatisfaction, product attributes, and the need for variation, on the switching of the Asus brand ". This data research used a questionnaire with a scale of 1-5 with a sample of 96 respondents. This sampling technique uses a non probability sampling with technique  purposive sampling . The data obtained were then analyzed with the SPSS . The results of this study partially (1) Dissatisfaction has a positive and significant effect on brand switching based on the value of t count > t table that is 3.575 > 1.662 with a significant 0.001 < 0.05. (2) Product attributes have a positive and significant effect on brand switching based on the value of t count > t table, namely 2.362 > 1.662 with a significant 0.002 < 0.05. (3). The need to look for variations has a positive and significant effect on brand switching based on the t count > t table, namely 6.472 > 1.662 with a significant 0.000 3.945 with a significant 0.000